(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article considers the features of the modern existence of the concept of bread based on a linguistic experiment. Several groups of subjects participated in the survey. To clarify the concept of bread, a linguistic experiment was conducted - a survey of a closed group of participants regarding the concept under study. The features of the existence of the concept of bread in the minds of modern native speakers were identified, the survey allows you to see the reflection of the concept of bread and changes in its perception in the minds of people belonging to different generations and professions. In the modern world, the bread lexeme has stable interpretations, which can be transmitted differently as an independent meaning or its shades in different dictionaries.